Cimicifoetisides A and B, two cytotoxic cycloartane triterpenoid glycosides from the rhizomes of Cimicifuga foetida, inhibit proliferation of cancer cells - Li-Rong Sun (Beilstein Journal of Organic Chemistry, 2007)
Two new cycloartane-type triterpene glycosides, namely cimicifoetisides A (1) and B (2), along with seven known compounds cimigenol, 25-O-acetylcimigenol, cimigenol 3-O-β-D-xylopyranoside, 12β-hydroxycimigenol 3-O-β-D-xylopyranoside, cimigenol 3-O-α-L-arabinopyranoside, 25-deoxyshengmanol 3-O-β-D-xylopyranoside and cimilactone A, were isolated from the rhizomes of Cimicifuga foetida. Their structures were elucidated as cimigenol 3-O-(2'-O-acetyl)-α-L-arabinopyranoside (1) and 25-O-acetylcimigenol 3-O-(2'-O-acetyl)-α-L-arabinopyranoside (2). Both compounds 1 and 2 exhibited potent cytotoxicity against rat EAC (Ehrlich ascites carcinoma) and MDA-MB-A231 (human breast cancer) cells with IC50 values of 0.52 and 6.74 μM for 1, and 0.19 and 10.21 μM for 2, suggesting their potential for further investigation as anti-cancer agents.